Conducting Randomized Controlled Trials of Complex Interventions in Prisons: A Sisyphean Task? - Charlotte Lennox; Sarah Leonard; Jane Senior; Caroline Hendricks; Sarah Rybczynska-Bunt; Cath Quinn; Richard Byng; Jenny Shaw (Frontiers in Psychiatry, 2022)
Randomized Controlled Trials (RCT) are the “gold standard” for measuring the effectiveness of an intervention. However, they have their limitations and are especially complex in prison settings. Several systematic reviews have highlighted some of the issues, including, institutional constraints e.g., “lock-downs,” follow-ups, contamination of allocation conditions and a reliance on self-report measures. In this article, we reflect on our experiences and will describe two RCTs. People in prison are a significantly disadvantaged and vulnerable group, ensuring equitable and effective interventions is key to reducing inequality and promoting positive outcomes. We ask are RCTs of complex interventions in prisons a sisyphean task? We certainly don't think so, but we propose that current accepted practice and research designs may be limiting our understanding and ability to test complex interventions in the real-world context of prisons. RCTs will always have their place, but designs need to be flexible and adaptive, with the development of other rigorous methods for evaluating impact of interventions e.g., non-randomized studies, including pre-post implementation studies. With robust research we can deliver quality evidence-based healthcare in prisons – after all the degree of civilization in a society is revealed by entering its prisons.